Largely forgotten: the Spanish judiciary of the 19th and 20th centuries as a problem of historical knowledge - Pérez Trujillano, Rubén (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2022)
This article addresses the historiographic landscape in Spain concerning the judiciary, focusing on judicial praxis. I conduct a comparative analysis with the aim of arguing the benefits of this kind of study for historical knowledge in general (2.1), and explore some of the causes for the prior neglect of this subject in Spanish historiography (2.2). This is followed by a critical analysis of studies of the judiciary during the Second Spanish Republic (1931- 1936), highlighting methodological shortcomings and pending lines of research (3.1 and 3.2). In light of the foregoing, I conclude that a historical analysis of judicial practice and reasoning is an urgent, unfinished task, not only in the field of legal and state historiography, and propose some methodological guidelines for further study of justice as political agency and an act of power (4).